ANALISA PROFITABILITAS RUMAH SAKIT YANG TERDAFTAR DI PASAR MODAL THAILAND DAN INDONESIA PADA TAHUN 2015-2019 - Carissa Faustina; Gracia S. Ugut (Fakultas Ekonomi dan Bisnis Universitas Atma Jaya Makassar, 2021)
The purpose of this study was conducted to determine the effect of COGS ratio, operating cost ratio, size, net working capital and leverage on profitability of healthcare in Indonesia and Thai. Sample used were 6 and 24 hospitals listed on Indonesian’s and Thai’s capital markets for period 2015 – 2019. Based on results with panel regression modeling, COGS ratio, leverage, size and Net Working Capital have a significant effect on Indonesian's ROA; size, leverage and Net Working Capital have a significant effect on Indonesian's ROE; Operating Expense Ratio and Size have a significant effect on Thai's ROA; and Net Working Capital, Size, and leverage have a significant effect on Thai's ROE. The R2 values obtained for ROA and ROE models in Indonesia were 91.08% and 97.99%, while Thai has 87.77% and 87.35%.